Selecting candidates for Deep Brain Stimulation in Parkinson's disease: the role of patients' expectations. (September 2019) - Geraedts, V.J.; Kuijf, M.L.; van Hilten, J.J.; Marinus, J.; Oosterloo, M.; Contarino, M.F.
Abstract: Patients with advanced Parkinson's Disease (PD) may be eligible for Deep Brain Stimulation (DBS) in case of medication-related motor fluctuations or tremor refractory to oral medication. However, several PD symptoms are unresponsive to DBS and constitute relative contra-indications for DBS. Patients referred for DBS undergo an eligibility screening during which motor functioning and contra-indications for surgery are assessed. During this pre-screening the potential benefits and drawbacks of surgery are discussed, together with patients' expectations of the results of DBS. Unrealistic expectations on the benefits of DBS may contribute to reduced patient satisfaction and poor clinical outcomes after surgery. The aim of this multicenter study (289 patients) was to assess the reasons for rejection after an outpatient-based pre-screening visit for DBS referrals, with particular emphasis on the role of patient expectations of DBS. The most frequent reason contributing to rejection was suboptimal oral treatment or satisfying symptom-control with oral medication (50% of rejections). Unrealistic expectations were identified in 38% of rejected patients and were the singular reason for rejection in 4%. Incorporating the assessment of unrealistic expectations increased the accuracy (Area Under the Curve) of determining DBS eligibility from 0.92 ((95% confidence interval (95%CI) 0.88–0.97) to 0.97 (95%CI 0.96–0.99). Patients' expectations of DBS are easily checked, and better education of patients and treating neurologists with regard to unrealistic expectations of this procedure may improve efficiency of referrals and avoid unnecessary stress and disappointments during screening. Highlights: DBS candidates with Parkinson's disease can be rejected for different reasons. Suboptimal or sufficient medical treatment are the main reasons for rejection. Unrealistic expectations of DBS contribute to the decision to reject. Assessment of DBS-expectations may improve efficiency of the screening procedure.